1972
DOI: 10.1021/jf60179a009
|View full text |Cite
|
Sign up to set email alerts
|

Volatile components in roast beef

Abstract: The volatile components of roast beef and roast beef drippings have been analyzed by gas-liquid chromatography (glc) and mass spectrometry (ms). Samples were prepared by low temperature, vacuum distillation of meat and drippings, followed by extraction of the distillates with diethyl ether. Major volatile components are alkanals, alk-2-enals, and alka-2,4-dienals. In addition t o these compounds the meat samples show high concentrations of 3-hydroxy-2-butanone and y-butyrolactone.Further classes of constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 12 publications
(13 reference statements)
1
32
0
Order By: Relevance
“…In fact, 2pentanone has been implicated in the off-flavour of cheddar cheese and the reversion flavour of soya bean oil30 whilst Liebich et al state that carbonyl compounds are important in roast beef aroma. 13 This agrees with a previous study in this laboratory and which also showed that the odour quality "roast meat" correlates positively with the terms "burnt" and "toasted".Zz Another interesting feature of the sample aged for 3 weeks is the low RPA value for the pyrazines in this sample compared with all others. Pyrazines are compounds associated with burnt and roasted notes in heated foods.34 If the burnt, toasted qualities of the 3 week-aged sample had been due to the pyrazines, then a high RPA for these compounds in this sampIe would have been expected.…”
Section: Chemical and Instrumental Analysismentioning
confidence: 99%
“…In fact, 2pentanone has been implicated in the off-flavour of cheddar cheese and the reversion flavour of soya bean oil30 whilst Liebich et al state that carbonyl compounds are important in roast beef aroma. 13 This agrees with a previous study in this laboratory and which also showed that the odour quality "roast meat" correlates positively with the terms "burnt" and "toasted".Zz Another interesting feature of the sample aged for 3 weeks is the low RPA value for the pyrazines in this sample compared with all others. Pyrazines are compounds associated with burnt and roasted notes in heated foods.34 If the burnt, toasted qualities of the 3 week-aged sample had been due to the pyrazines, then a high RPA for these compounds in this sampIe would have been expected.…”
Section: Chemical and Instrumental Analysismentioning
confidence: 99%
“…Its origin and formation in heated beer has also been studied (291). Nonenal (C-24) was also detected in various food products such as carrot root oil (290), tomato (219), beef (292), and cranberry (293). Numerous unsaturated aldehydes have also been identified in cooked chicken flavor (294).…”
Section: Aldehydesmentioning
confidence: 99%
“…It was shown by Peer and van den Ouweland (1968) that 4-hydroxy-5-methyl-3-(2H)-furanone can be prepared from n-ribose-5-phosphate in concentrated buffer systems at pH 5.5. Liebich et al (1972) studied the volatile components of roast beef by gas-liquid chromatography and mass spectrometry. Brinkman et al (1972) analyzed the volatiles of the headspace of beef broth, and found the following: 3-methyl-butanol, benzaldehyde, and 3,5-dimethyl-1,2,4-trithiolane (cis and trans).…”
Section: Volathe Flavorsmentioning
confidence: 99%